2021
DOI: 10.15252/emmm.202114073
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intrinsic inhibitory checkpoints using nano‐carriers to unleash NK cell activity

Abstract: Natural killer (NK) cells provide a powerful weapon mediating immune defense against viral infections, tumor growth, and metastatic spread. NK cells demonstrate great potential for cancer immunotherapy; they can rapidly and directly kill cancer cells in the absence of MHC-dependent antigen presentation and can initiate a robust immune response in the tumor microenvironment (TME). Nevertheless, current NK cell-based immunotherapies have several drawbacks, such as the requirement for ex vivo expansion of modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 84 publications
0
25
0
1
Order By: Relevance
“…We recently showed that ARF and Protein Kinase C (PKC)θ play an important role in determining the SHP-1 conformational structure and its impact on NK cell activity [ 9 , 33 ]. Along these lines, we also demonstrated that silencing of SHP-1 upon inhibitory synapse engagement improves NK cell cytotoxic potential [ 34 ]. In the current study, we demonstrate that the SHP-1-ARF axis is governed by WASp, the actin nucleation-promoting factor that dictates the NK cell immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that ARF and Protein Kinase C (PKC)θ play an important role in determining the SHP-1 conformational structure and its impact on NK cell activity [ 9 , 33 ]. Along these lines, we also demonstrated that silencing of SHP-1 upon inhibitory synapse engagement improves NK cell cytotoxic potential [ 34 ]. In the current study, we demonstrate that the SHP-1-ARF axis is governed by WASp, the actin nucleation-promoting factor that dictates the NK cell immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were centrifuged, supernatant was cleared, and the cells were re-suspended in lysis buffer as previously described [ 9 , 33 , 34 ]. Cells were placed on ice for 30 min and then centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a non-viral lipid nanoparticle (NP)-based delivery system containing small interfering RNAs (siRNAs) has successfully silenced the main intracellular NK checkpoints, c-Cbl, Cbl-b, and SHP-1, in vivo [28]. Such checkpoint blockade unleashes NK cell activity and enhances NK cytotoxicity in the tumor microenvironment [28].…”
Section: Cbl-b and C-cblmentioning
confidence: 99%
“…Recently, a non-viral lipid nanoparticle (NP)-based delivery system containing small interfering RNAs (siRNAs) has successfully silenced the main intracellular NK checkpoints, c-Cbl, Cbl-b, and SHP-1, in vivo [28]. Such checkpoint blockade unleashes NK cell activity and enhances NK cytotoxicity in the tumor microenvironment [28]. Besides, since these nanoparticles directly target NK cells in vivo, there is no need for ex vivo expansion of NK cells, which has been a major drawback of current NK cell-based immunotherapies [28].…”
Section: Cbl-b and C-cblmentioning
confidence: 99%
See 1 more Smart Citation